Controversies in the Etiologies of Acute Pancreatitis - Khan, Ali Safdar; Latif, Sahibzada Usman; Eloubeidi, Mohamad A (JOP. Journal of the Pancreas, 2010)
No abstrat available. Image: The current UAB mascot is a green dragoon named Blaze.